2013
DOI: 10.3109/07357907.2013.820319
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Salivary Protein Secretions as anIn VivoModel to Study Mantel Cell Lymphoma Progression and Treatment

Abstract: The results of the study suggest salivary protein alterations secondary to MCL and that a number of the proteins were changed as a result of chemotherapeutic intervention suggesting that the treatment, from a proteomic perspective, was efficacious. The study suggests that salivary secretions may be used as in vivo model for studying MCL progression and treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Despite numerous research studies on salivary biomarkers, saliva monitoring still is in its infancy. Streckfus et al [ 87 ] observed pre-, peri- and post-chemotherapy variations in the salivary protein profile of an individual with Mantel cell lymphoma, suggesting the use of saliva for controlling disease progression.…”
Section: Systemic Cancer and Salivamentioning
confidence: 99%
“…Despite numerous research studies on salivary biomarkers, saliva monitoring still is in its infancy. Streckfus et al [ 87 ] observed pre-, peri- and post-chemotherapy variations in the salivary protein profile of an individual with Mantel cell lymphoma, suggesting the use of saliva for controlling disease progression.…”
Section: Systemic Cancer and Salivamentioning
confidence: 99%
“…In spite of the power of the t(11;14)(q1;q32) translocation as a hallmark of MCL, other disease markers would be valuable for both diagnosis and as potential treatment targets, warranting further study of CD148 in this tumor. A study directly assessing treatment response in MCL was performed by Streckfus et al . They characterized the proteome from specimens of saliva before, during, and after therapy for MCL .…”
Section: Biomarker Discovery In Lymphoma Patient Samples By a Proteommentioning
confidence: 99%
“…A study directly assessing treatment response in MCL was performed by Streckfus et al . They characterized the proteome from specimens of saliva before, during, and after therapy for MCL . 2D DIGE and subsequent identification by LC‐MS/MS was used to identify differences in protein profiles from one patient with a sample at time of recurrence (pretreatment) and a second sample at time of remission (posttreatment).…”
Section: Biomarker Discovery In Lymphoma Patient Samples By a Proteommentioning
confidence: 99%
“…The author would like to add two more items: (1) ascertain methods to determine the efficacy of treatment and (2) ascertain methods to determine that the treated patient is not only in clinical remission, but in molecular remission as well [13,14]. The latter action items would assure successful treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, there remains a necessity to identify novel approaches that improve breast cancer screening and early detection. This, in turn, reduces the problems of over-diagnosis and over-treatment and can detect cancers at a point where interventions maybe more effective [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%